Systematic Literature Review: The Role Of Product Quality And Digital Promotion On Purchasing Decisions - Wahyudi, Eko Juni; Friyanto, Friyanto; Borahima, Bahrun; Sudarjo, Sudarjo (Universitas Islam Kadiri, 2024)
The role of product quality and promotion in the sales context is extremely important. Customer perceptions of value and satisfaction with a product are influenced by product consistency. With promotions on digital platforms, information about product quality can be easily found by all consumers from various regions, either by online reviews, customer testimonials, or content shared by the company itself. This report aims to answer questions about the effect of product quality and promotion on purchasing decisions. Researchers used the systematic literature review approach to find 176 national articles that were endorsed by sinta in a search using publish or perish and other programs such as zotero, & mendeley, which were then sorted into 45 selected articles for descriptive analysis. Brands can increase their visibility and build stronger links with their target audiences by using the right digital marketing techniques, such as internet advertising, social media campaigns, and content marketing. In terms of satisfaction, brand reputation, loyalty, and differentiation from competitors, product quality plays a vital role in making purchasing decisions. Therefore, both product quality and effective promotion play a vital role in creating value for customers and strengthening a brand's position in the market.